Radiation-hygienic situation in the area of sublimate production waste storage of JSC “AECC” - Yu. N. Zozul; S. M. Kiselev; V. V. Shlygin; S. V. Akhromeev; A. N. Malakhova; T. I. Gimadova; Yu. S. Belskikh; Yu. V. Archakova; L. N. Galitskaya (Радиационная гигиена)
In accordance with the fundamentals of state policy in the field of ensuring nuclear and radiation safety, State Corporation «Rosatom» carries out the remediation of JSC “AECC” nuclear legacy sites. The article presents the results of environmental impact assessment carried out in 2021-2023 in the vicinity of sublimation waste storage facilities that are being decommissioned. Health physics studies involved ambient dose rate measurements, sampling (soil, groundwater) and analysis of radiological and non radiological environmental pollutants. The external gamma dose rate, as well as content of natural and artificial radionuclides in soil, don’t exceed background levels. While uranium presence in groundwater is found to be 10 times and higher then background level. The data obtained indicate that the accumulated wastes of sludge sumps (bottom sediments, pulp) сome into contact with natural water. Flooded storage facilities form a plume of contamination spreading out in the direction of groundwater flow. Given the current situation optimization of the existing environmental monitoring programs in the JSC “AECC” health protection zone is recommended and reference levels of uranium proposed.